Analysis of Consumer Technology Acceptance Model on Indonesian Telemedicine Applications - Alfarizi, Muhammad (SBM ITB, 2022)
Abstract. The digital era makes it easier for humans to cope with pandemic-related confinement, including in terms of access to healthcare. Health e-commerce facilitates consumers' access to healthcare and pharmaceuticals without having to leave the house, and startups in the health sector can contribute to economic growth and a culture of healthy living. This study gauges consumer perceptions as related to the purchase of medicines and doctor consultations online through telemedicine platforms in Indonesia. More specifically, we use the technology acceptance model to investigate how consumer perceptions on the quality, services, and products of both web- and application-based platforms influence consumer purchasing intentions for online health consultations and prescription and non-prescription medicines. Our data comprise the responses of 250 survey participants, analyzed via structural equation modeling techniques. The results show that trust can play a positive role in determining consumer intentions to purchase health consultation services or medicines through telemedicine platforms in Indonesia. Moreover, they show that 1) e-commerce telemedicine can earn greater consumer confidence via the improvement of product and service perceptions, and 2) websites and applications can ensure consumer trust via the improvement of website quality and service perceptions. The analysis of our research findings indicates that the quality of websites, applications, services, and product perceptions determine trust, and hence build consumer confidence in shopping for health products or for online consultations with competent doctors.Keyword: Covid-19, digitization, consumer , start up, telemedicineAbstract. Era digital memudahkan manusia ketika harus terkurung dalam pandemi Covid-19, termasuk akses kesehatan. Health e-Commerce hadir untuk memudahkan konsumen mendapatkan akses transaksi kesehatan dan obat tanpa harus keluar rumah. Secara tidak langsung, kehadiran Start-Up di bidang kesehatan memberikan kontribusi yang signifikan terhadap pertumbuhan ekonomi dan budaya hidup sehat. Penelitian ini bertujuan untuk mengetahui persepsi konsumen terhadap pembelian obat dan jasa konsultasi dokter secara online melalui platform telemedicine di Indonesia. Model penerimaan teknologi digunakan untuk menyelidiki peran kualitas web dan aplikasi, persepsi layanan dan produk pada niat konsumen untuk konsultasi kesehatan online dan pembelian obat resep dan non-resep. Sebanyak 250 responden disurvei dan data dianalisis menggunakan teknik pemodelan persamaan struktural. Hasil penelitian menunjukkan bahwa kepercayaan berperan positif dalam menentukan niat konsumen untuk menggunakan jasa konsultasi dokter atau membeli obat melalui platform Telemedicine di Indonesia. Hasil penelitian menunjukkan bahwa E-Commerce Telemedicine dapat meningkatkan kepercayaan konsumen secara signifikan dengan meningkatkan persepsi produk dan layanan, sedangkan situs web dan sistem aplikasi dapat memastikan kepercayaan konsumen dengan meningkatkan kualitas situs web dan persepsi layanan. Analisis hasil penelitian ini berarti bahwa kualitas website, sistem aplikasi, layanan, dan persepsi produk menentukan kepercayaan, dan mereka membangun kepercayaan konsumen dalam berbelanja produk kesehatan atau konsultasi online dengan dokter yang kompeten.Kata kunci: Covid-19, digitalisasi, konsumen , start Up, telemedicine